A 3-dimensional histology computer model of malignant melanoma and its implications for digital pathology - Kurz, Alexander; Krahl, Dieter; Kutzner, Heinz; Barnhill, Raymond; Perasole, Antonio; Figueras, Maria Teresa Fernandez; Ferrara, Gerardo; Braun, Stephan A.; Starz, Hans; Llamas-Velasco, Mar; Utikal, Jochen; Fröhling, Stefan; et al. (European journal of cancer, 2023)
Historically, cancer diagnoses have been made by pathologists using two-dimensional histological slides. However, with the advent of digital pathology and artificial intelligence, slides are being digitised, providing new opportunities to integrate their information. Since nature is 3-dimensional (3D), it seems intuitive to digitally reassemble the 3D structure for diagnosis. Objective: To develop the first human-3D-melanoma-histology-model with full data and code availability. Further, to evaluate the 3D-simulation together with experienced pathologists in the field and discuss the implications of digital 3D-models for the future of digital pathology.